REGENERASI SIRIP KAUDAL IKAN GATUL (Poecilia sp.) YANG MENGALAMI MALFORMASI - Nikmatul Iza; Dwi Listyorini; Abdul Gofur (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2016)
Gatul fish in included in the family Poecilidae which is a small fresh water, male is smaller and more colorfull than female. This fish is easy to be taken care in laboratory and has a short reproduction cycle, thus allowing these fish to be one animal model development in the field of biology. Yet, in Indonesia the biological study upon Gatul fish is very limited. The aim of this study is to understand the process of caudal fin regeneration of Gatul fish are malformation (abnormal growth). Caudal fin of Gatul fish were vertically cut in a half of its length. Observation was done using 400x magnification. Picture with taken by camera with digital zooming. The subject of this study with a body length of 2-3 cm. The result shows that regeneration of Gatul caudal fin is started with wound healing in day-1 (D1= 24 hours after amputation) and blastema formation, then stump regeneration begin to grow in D2. Regenerative outgrowth begin in D3 characterized by the formation Blood island and fin rays. Differentiation begin in D6 and extended up to D18. From this research we can conclude that the process is going step by step through wound healing, stump growth, and tissue differentiation, and respectively